Rare kidney diseases: from clinical manifestations to diagnosis - Schieppati, Arrigo (Contributions to nephrology, 2001)
Patients with rare disorders are often condemned to neglect: their disease is difficult to recognize, the information available on possible therapies is scanty (if there exists one at all) and, due to small patient populations, little research is done in the field. However, there are several examples of how research into the etiology and pathogenesis of rare renal disorders has provided important information on the normal physiology of the kidney. Featuring reviews by leading experts in their field, this volume offers up-to-date information on a number of uncommon renal disorders, including Fabry Disease, von Hippel-Lindau Disease, tuberous sclerosis, autosomal recessive polycystic disease, medullary cystic disease, Alport Syndrome, Liddles Syndrome, primary hyperoxaluria, systemic vasculitis and familial and recurrent hemolytic uremic syndrome. A chapter on gene therapy in nephrology is also included.This book will be important reading for all those involved in basic and clinical research of the kidney. Moreover, it will provide valuable information for the practicing nephrologist wishing to learn more about how to recognize serious but neglected renal disorders